The effect of alternative fuels on gaseous and particulate matter (PM) emission performance in an auxiliary power unit (APU). (May 2019) - Khandelwal, B.; Cronly, J.; Ahmed, I.S.; Wijesinghe, C.J.; Lewis, C.
ABSTRACT: There is a growing interest in the use of alternative fuels in gas turbine engines to reduce emissions. Testing of alternative fuels is expensive when done on a large-scale gas turbine engine. In this study, a re-commissioned small gas turbine auxiliary power unit (APU) has been used to test various blends of Jet A-1, synthetic paraffinic kerosene (SPK) and diesel with as well as eight other novel fuels. A detailed analysis of performance, gaseous emissions and particulate emissions has been presented in this study. It is observed that aromatic content in general as well as the particular chemical composition of the aromatic compound plays a vital role in particulate emissions generation. SPK fuel shows substantially lower particulate emissions with respect to Jet A. However, not all the species of aromatics negatively impact particulate emissions. Gaseous emissions measured are comparable for all the fuels tested in this study.